(untitled) (European Journal of Economics, Finance and Business Development, 2025)
Reforms are being implemented in Uzbekistan to develop the rule of law and human capital, to build a fair and strong civil society, and to further improve the living conditions of the population. In this article, the development of human capital - intellectual ability is one of the urgent issues of today and the need to strengthen its regulatory and legal foundations.